Skimming y scanning para la comprensión literal e inferencial en Inglés (2022)
Eng: This paper presents a research process which objective was to strengthen the literal and inferential levels of reading comprehension in English through the use of skimming and scanning techniques with 10th and 11th grade students, from an Official Educational Institution of Santa Sofía municipality, in Boyacá. This study was approached from the action-research design through a qualitative approach, the data were obtained through the analysis of didactic guides developed by the students, the researcher's field notes and the application of an input and output reading comprehension test. The results show that the application of the two reading techniques has a positive impact on reading performance at the literal level mainly and, to a lesser degree, in the inferential reading dimension, through the correlation of three conditions: the reader's linguistic competence level, the relevance of his/her prior knowledge, and the external and internal characteristics of the text to be read.